Association of body mass index and perinatal outcomes of women delivering at advanced maternal age - Guimin Yan; Ying Dong; Xiaojuan Yu; Lin Zhang; Xin Zhao; Jing Zhou; Yan Du; Ling Wang (World Scientific Publishing, 2024)
Purpose: To explore the association between body mass index (BMI) and perinatal outcomes of women delivering at advanced maternal age (AMA). Patients and methods: In this retrospective study, 261 Chinese women aged 35 and above who delivered from January 1st to June 30th, 2021 at Shanghai Putuo Maternity and Infant Health Hospital were enrolled. Information including height, pre-pregnancy and prenatal weight, and maternal and neonatal complications was recorded. Women were classified into the normal group ([Formula: see text][Formula: see text]kg/m2, [Formula: see text], 82.4%) and overweight group (BMI: [Formula: see text][Formula: see text]kg/m2, [Formula: see text], 17.6%) based on their pre-pregnancy BMI. Women were further categorized based on their BMI gains during pregnancy: group A (BMI gain [Formula: see text][Formula: see text]kg/m2) and group B (BMI gain [Formula: see text][Formula: see text]kg/m2). The association of perinatal outcomes and pre-pregnancy BMI was investigated based on BMI gain strata. Results: Of women in the overweight group, the risk of gestational diabetes mellitus (GDM) and cesarean section (CS) were significantly higher than that of the normal group ([Formula: see text]). Furthermore, we found overweight women had a higher risk of CS when their BMI gain was [Formula: see text][Formula: see text]kg/m2 and a higher incidence of GDM when their BMI gain [Formula: see text][Formula: see text]kg/m2 (both [Formula: see text]). Conclusion: Adverse perinatal complications that occur in AMA women are associated with overweight and excessive BMI gain during pregnancy. Effective management of weight around pregnancy may reduce adverse outcomes.